Rethinking sexual minority rights in the context of Zimbabwean constitution. - Muganyi, Tanaka (Midlands State University, 2020)
The subject of sexual minority rights is a very controversial issue in the African society. The conventional understanding of sexual minority rights draws its inspiration from culture and religion to the effect that such conduct is unnatural, taboo and has no place in the African social system. Zimbabwe mirrors this conceptualisation of sexual minority rights and both laws and jurisprudence have depicted this intolerance, opting to be associated with the conventional view that shuns sexual minorities. While such is the prevalent ethos, proponents for sexual minority rights have however castigated this discriminatory tendencies in Zimbabwe arguing that laws and conduct that discriminates sexual minority groups run afoul of the international human rights regime. Zimbabweans embraced a new Constitution in 2013 which has an elaborate declaration of rights with the non-discrimination clause (Section 56) as one of the fundamental provisions therein. It is against this development that this study seeks to explore the sustainability of the intolerance towards sexual minorities, legally insofar as Zimbabwe’s Constitution is concerned. It is argued herein that albeit the socio-cultural and religious motives attached to this subject, sexual minority rights must be treated as a human rights issue pursuant to understanding the arguments posed for and against embracing them.